2023
DOI: 10.1007/s41347-023-00299-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Psychoeducational Group to Expand Mobile Application Knowledge and Use in a Veteran Residential Treatment Program

Abstract: Despite the availability of free, evidence-informed mental health mobile applications (apps) to support Veterans and Service Members, interventions are needed to ensure patients are aware of the developed resources. A psychoeducational group was developed and evaluated by a quality improvement project in the context of a Department of Veterans Affairs residential treatment program. Four weekly group sessions introduced 82 Veterans to two similarly themed apps at each group and supported Veteran installation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A study by Harned et al. (2023) implemented a psychoeducational group to expand knowledge and use of mobile health applications among veterans. Individuals at a VA residential treatment program ( n = 82) attended four weekly psychoeducational groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Harned et al. (2023) implemented a psychoeducational group to expand knowledge and use of mobile health applications among veterans. Individuals at a VA residential treatment program ( n = 82) attended four weekly psychoeducational groups.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to group participation, 29.4% of participants reported hearing about the VHB while 9.9% reported using it. After the group, 44% of the participants noted that they found the VHB helpful and 46% indicated that they intended to use the VHB in the future (Harned et al., 2023). Results may have been impacted by the fact that suicidal ideation or self‐perceived suicide risk was rare among participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 Though privacy is a reasonable and foreseeable concern, there are already experiences implementing such software in compliance with the Health Insurance Portability and Accountability Act. 28 , 65 Apart from smart devices, braces and sleeves have technology that allows continuous patient monitoring in their daily living and/or sports activity. 32 , 44 One example is the motusBASEBALL sleeve (Motus Global Inc., Massapequa, NY, USA) that houses a small inertial measurement unit that allows measuring throw counts, peak elbow varus torque, arm speed, arm slot, maximum shoulder rotation, and workload.…”
Section: Evaluation Of Clinical Outcomesmentioning
confidence: 99%